Synthesis and nonlinear-optical properties of vinyl-addition poly(norbornene)s - Park, KH; Twieg, RJ; Ravikiran, R; Rhodes, LF; Shick, RA; Yankelevich, D; Knoesen, A (AMER CHEMICAL SOC, 2004)
Vinyl-addition poly(norbornene) copolymers functionalized with nonlinear optical chromophore side groups have been prepared using (eta(6)-toluene)Ni(C6F5)(2), and their electrooptic properties have been characterized. The nickel complex used to polymerize the norbornene monomers is tolerant to many functional groups found in nonlinear optical chromophores although nitriles and amines other than trisubstituted amines strongly inhibit the reaction. A vinyl-addition copolymer of hexylnorbornene and a norbornene-functionalized Disperse Red 1 chromophore was scaled up and studied in detail. Initial studies indicate that electric field poling is effective but that relaxation of polar order in the poly(norbornene) is faster than in a comparable methacrylate copolymer.
Keywords: OPENING METATHESIS POLYMERIZATION; LIQUID-CRYSTALLINE POLYMERS; THERMAL-STABILITY; CHROMOPHORES; NORBORNENE; POLYNORBORNENES; CATALYSTS; 2ND